The epidemiology of nasopharyngeal colonisation of Streptococcus pneumoniae in children with respiratory tract infection [Solunum yolu enfeksiyonu olan çocuklarda nazofarenksde Streptococcus pneumoniae kolonizasyon epidemiyolojisi] - (:unkn) unknown (My University, 2004)
Nasopharyngeal swab specimens from 324 children with respiratory tract infections were evaluated to detect the rate of Streptococcus pneumoniae colonisation. S.pneumoniae was detected in 92 (28%) of the subjects. Forty three (46.7%) of the isolates were serotyped by the capsular swelling tests. The most common serotypes were 19F, 6B, 3 and 23F. The 7, 9 and 11 valent conjugate pneumococcal vaccines covered 35.8%, 40% and 46.7% of all the S.pneumoniae isolates, respectively. Thirty two (34.8%) isolates exhibited penicillin MIC values between 0.1 and 1 μg/ ml, only 1 isolate had MIC ≥2 μ/ml. Penicillin resistant pneumococcal colonisation was most frequently detected in children with viral upper respiratory tract infections (12.5%). Resistance rates of trimetoprim- sulfamethoxazole, erythromycin, chloramphenicol, clindamycin, ceftriaxone, rifampin were 31.5%, 9.8%, 6.5%, 4.3%, 1%, 0%, respectively. Being a children of a family with low income was the only risk factor for colonisation with S.pneumoniae, whereas having a sibling attending to a day care center, antibiotic use in the last three months and use of more than one antibiotic were significant risk factors for colonisation with penicillin resistant S.pneumoniae (p<0.05).
Keywords: Antibiotic resistance; Nasopharyngeal colonisation; Serotyping; Streptococcus pneumoniae